Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13195-022-01020-9
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine and olanzapine block apoE4-catalyzed polymerization of Aβ and show evidence of improving Alzheimer’s disease cognition

Abstract: Background The apolipoprotein E (APOE) ε4 allele confers the strongest risk for late-onset Alzheimer’s disease (AD) besides age itself, but the mechanisms underlying this risk are debated. One hypothesis supported by evidence from multiple labs is that apoE4 binds to the amyloid-β (Aβ) peptide and catalyzes its polymerization into neurotoxic oligomers and fibrils. Inhibiting this early step in the amyloid cascade may thereby reduce or prevent neurodegeneration and AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The inhalation of PNO in both concentrations resulted in significant increases in the swimming time ( p = 0.0003 for 1% PNO and p = 0.0022 for 3% PNO) ( Figure 3 A) as well as significant reductions of the immobility time ( p = 0.0001 for 1% PNO and p = 0.0015 for 3% PNO) ( Figure 3 B). Imipramine (Imp), a tricyclic antidepressant, also assessed as a disease-modifying treatment for AD [ 89 ], has been used as a positive control within the FST.…”
Section: Resultsmentioning
confidence: 99%
“…The inhalation of PNO in both concentrations resulted in significant increases in the swimming time ( p = 0.0003 for 1% PNO and p = 0.0022 for 3% PNO) ( Figure 3 A) as well as significant reductions of the immobility time ( p = 0.0001 for 1% PNO and p = 0.0015 for 3% PNO) ( Figure 3 B). Imipramine (Imp), a tricyclic antidepressant, also assessed as a disease-modifying treatment for AD [ 89 ], has been used as a positive control within the FST.…”
Section: Resultsmentioning
confidence: 99%
“…In a study to identify small molecules that prevent the interaction between apoE4 and Aβ, ThT assay was used. 28 The assay was able to monitor Aβ fibrillization and study the catalytic effects of apoE4, then was optimized to be used in HTS and identify inhibitors of apoE4-Aβ interaction. A drug screen was conducted using 595 compounds from the NIH Clinical Collection (NCC) library, resulting in the identification of 134 hits.…”
Section: ■ Bioassay Screeningmentioning
confidence: 99%
“…In a study to identify small molecules that prevent the interaction between apoE4 and Aβ, ThT assay was used . The assay was able to monitor Aβ fibrillization and study the catalytic effects of apoE4, then was optimized to be used in HTS and identify inhibitors of apoE4-Aβ interaction.…”
Section: Bioassay Screeningmentioning
confidence: 99%
“…Liu et al found that the inhibition of its interaction with Aβ using CPO-Aβ17–21 peptide led to a decrease in cognitive impairment and neuroprotection in an AD APP/PS1 transgenic mouse model [ 122 ]. Recent studies have shown that blocking the ability of APOE to initiate Aβ oligomerization also has a therapeutic effect—a similar approach has been successfully tested in imipramine and olanzapine preparations on 5xFAD transgenic mice, TgF344-AD transgenic rats, and a primary neuronal culture obtained from these animals [ 123 ].…”
Section: Chemicals Targeting Aβ and Its Intermolecular Complexesmentioning
confidence: 99%